Cenzura poezije v 80. letih 20. stoletja - Gardocki, Wiktor (Slavistična revija, 2019)
This article examines the topic of poetry censorship in the 1980s. The first part discusses the complex legal and political conditions, including subsequent changes to the Censorship Act (Ustawa o cenzurze), as they relate to the literary works. Next, I present the publishing history of censored poems and poems withheld from publication. The article is based on extensive archival research. Most of the documents I examine have not previously been published.
Keywords: 1980-1990; Glavni urad za nadzor tiska, publikacij in videa; Polish literature; Polish People's Republic; Polish poetry; Polish poets; poljska književnost; Poljska ljudska republika; poljska poezija; poljski pesniki; The Main Office of Control of Press, publications and shows